The protective role of self-esteem on burnout and depression symptoms among police officers: A path analysis approach - Pikoulas, Georgios (International journal of police science & management, 2022)
The aim of this cross-sectional study is to investigate the effect of self-esteem on burnout symptoms and depression, using a path analysis approach. A total of 396 Greek police officers, 145 female and 251 male, with a mean age of 37.7 years, participated in the study. The questionnaire included: (a) social–demographic characteristics, (b) Rosenberg's self-esteem scale, (c) Zung's depression scale, and (d) Maslach's burnout scale. Analysis of variance was applied to find whether the demographic variables of gender, age and urban/rural location had a significant effect on the examined psychometric scales. A path model was then tested, aiming to quantify the direct and indirect effects of age, working location and self-esteem on depression and burnout symptoms. Emotional exhaustion and personal accomplishment scores were found to have a direct effect on depression and completely explained the effect of urban area on depression. Self-esteem was found to be a significant regressor on depression and the three burnout subscales, while older and more experienced officers had significantly lower burnout symptoms. The findings of the study confirm the protective role of self-esteem. The findings also confirmed that police officers working in an urban environment are at a greater risk of developing burnout and depression symptoms, while the depressed feelings of police officers in an urban area are completely explained by increased feelings of burnout. The ability of police officers to counteract the psycho-emotional pressure of their profession as they age in service is demonstrated. The need for initiatives aiming to support young officers and police personnel working in large cities is indicated.